Das Public Kapital : How Much Would Higher German Public Investment Help Germany and the Euro Area? - Elekdag, Selim (IMF Working Papers; Working Paper ;, 2014)
Given the backdrop of pressing infrastructure needs, this paper argues that higher German public investment would not only stimulate domestic demand in the near term and reduce the current account surplus, but would also raise output over the longer-run as well as generate beneficial regional spillovers. While time-to-build delays can weaken the impact of the stimulus in the short-run, the expansionary effects of higher public investment are substantially strengthened with an accommodative monetary policy stance-as is typical during periods of economic slack. The current low-interest rate environment presents a window of opportunity to finance higher public investment at historically favorable rates.